2004
DOI: 10.1002/bies.20010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic proofreading by the cavity system of myoglobin: protection from poisoning

Abstract: Throughout its matrix of atoms, myoglobin has a network of cavities that are inhabited for short lengths of time by ligands released by photolysis from the myoglobin heme. The purpose or effect of this cavity network is not clear. A recently published kinetic scheme that fits data from many native and mutant myoglobin oxygen photolysis experiments can be modified easily into a kinetic scheme that includes kinetic proofreading. Proofreading would provide protection against contaminants and, specifically, might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 103 publications
2
17
0
Order By: Relevance
“…b Relative CO occupancy (in percent) of each site calculated from the sum of occurrences in all trajectories at 200, 300, or 320 K. their distribution and localization inside proteins, as well as their hydration. Both crystallographic studies and MD simulations performed on wild-type or mutant myoglobins (Elber and Karplus 1990;Carlson et al 1996;Hummer et al 2004;Radding and Phillips 2004;Bossa et al 2005), hemoglobin , and truncated Hb (Milani et al 2004) suggested that internal cavities play a functional role and partly determine the protein reactivity by defining preferred diffusion pathways and providing transient docking sites for ligands.…”
Section: Internal Cavitiesmentioning
confidence: 99%
“…b Relative CO occupancy (in percent) of each site calculated from the sum of occurrences in all trajectories at 200, 300, or 320 K. their distribution and localization inside proteins, as well as their hydration. Both crystallographic studies and MD simulations performed on wild-type or mutant myoglobins (Elber and Karplus 1990;Carlson et al 1996;Hummer et al 2004;Radding and Phillips 2004;Bossa et al 2005), hemoglobin , and truncated Hb (Milani et al 2004) suggested that internal cavities play a functional role and partly determine the protein reactivity by defining preferred diffusion pathways and providing transient docking sites for ligands.…”
Section: Internal Cavitiesmentioning
confidence: 99%
“…Mb is a small globular protein that functions as an oxygen transport, storage, and mobile buffer protein in muscle 24. Mb folds as a compact monomer and does not undergo large conformational changes in comparison with multidomain proteins, but localized changes are observed17 as it reversibly binds various ligands,11, 25 and with pH variation 26.…”
Section: Introductionmentioning
confidence: 99%
“…Myoglobin (Mb) is a heme protein that reversibly binds diatomic oxygen and other small gaseous ligands such as carbon monoxide (CO) and nitric oxide and serves as a mobile oxygen buffer in muscle (Radding & Phillips, 2004;Springer et al, 1994). Owing to its simple well characterized structure, the presence of a photolabile bond between the ligand and the heme iron (Gibson & Ainsworth, 1957) and the availability of a large number of mutants with altered functional and kinetic properties, Mb is an appealing model for protein dynamics and has been thoroughly studied by various biophysical techniques (Brunori et al, 2004;Bourgeois et al, 2003;Nienhaus et al, 2003;Srajer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%